2018
DOI: 10.7717/peerj.6083
|View full text |Cite
|
Sign up to set email alerts
|

Ranaviruses and reptiles

Abstract: Ranaviruses can infect many vertebrate classes including fish, amphibians and reptiles, but for the most part, research has been focused on non-reptilian hosts, amphibians in particular. More recently, reports of ranaviral infections of reptiles are increasing with over 12 families of reptiles currently susceptible to ranaviral infection. Reptiles are infected by ranaviruses that are genetically similar to, or the same as, the viruses that infect amphibians and fish; however, physiological and ecological diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 117 publications
1
20
1
2
Order By: Relevance
“…Basking, a possible form of behavioural fever, was observed more frequently in higher dose groups; however, the thermal potential was not assessed, and turtles may have just been escaping the water and not thermoregulating [31]. Skin lesions reported in our study have not been reported in other turtle challenge studies, but external skin lesions are often reported in lizards with ranaviral infections [3] and ulceration has been reported in a ranaviral infection of eastern box turtles [32]. Skin lesions were only found in the i.m.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Basking, a possible form of behavioural fever, was observed more frequently in higher dose groups; however, the thermal potential was not assessed, and turtles may have just been escaping the water and not thermoregulating [31]. Skin lesions reported in our study have not been reported in other turtle challenge studies, but external skin lesions are often reported in lizards with ranaviral infections [3] and ulceration has been reported in a ranaviral infection of eastern box turtles [32]. Skin lesions were only found in the i.m.…”
Section: Discussioncontrasting
confidence: 54%
“…For the most part, ranaviral disease research has focused on fish and amphibians, but these viruses also cause disease in wild and captive reptile species around the world, often resulting in high levels of mortality [2]. The most common group of reptiles to be reported with ranaviral disease are turtles (order Testudines) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of microbiomes in both human health [14, 15] and emerging infectious diseases in groups like amphibians [16–18], it is likely that microbiomes are important for turtle health as well. Furthermore, Ranavirus infections are of particular concern for turtles [19] and Ranavirus infections are negatively associated with higher microbial richness in amphibians [20], suggesting that microbiomes may be able to mitigate infections.…”
Section: Introductionmentioning
confidence: 99%
“…Reptile ranaviruses have a multispecies host range, and therefore reptile-specific PCR assays are not required (Wirth et al, 2018).…”
Section: Methodsmentioning
confidence: 99%